2022
DOI: 10.35848/1347-4065/ac5adc
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation during collision for anti-relaxation coatings in alkali-metal vapor cells

Abstract: In this paper, we proposed a method to characterise the coating performance of alkali-metal cells by directly measuring the energy dissipation during collisions between the anti-relaxation coating surface and atoms in the cell. We confirmed that the energy dissipation during collisions is positively correlated with the relaxation characteristics of alkali metals at various temperatures. This discovery is of great significance as it can be utilised to characterise the anti-relaxation coating performance of alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…There was no uniform temperature increase law for energy dissipation. Our previous work 36 showed that the thermal change of energy dissipation for hexatriacontane coating baked for 15 min matches the temperature-rising trend of the relaxation rate in the paraffin-coated cell, that decreased first and then increased. This phenomenon is inconsistent with the current observation.…”
Section: ■ Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…There was no uniform temperature increase law for energy dissipation. Our previous work 36 showed that the thermal change of energy dissipation for hexatriacontane coating baked for 15 min matches the temperature-rising trend of the relaxation rate in the paraffin-coated cell, that decreased first and then increased. This phenomenon is inconsistent with the current observation.…”
Section: ■ Introductionmentioning
confidence: 77%
“…Dong et al observed a correlation between the temperature-rising law of relaxation rate of coated-cells and the collision energy dissipation between the AFM probe tip and the slide coating, where it decreases first and then increases. As a result, this study concludes that energy dissipation can be used to quantitatively evaluate the cell relaxation property and its thermal changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic force microscopy (AFM) has been used by Dong et al 10 to study energy dissipation on the surface coating of a magnetometer cell wall, where the energy dissipation between the AFM tip and the surface coating is assumed approximately equal to the adsorption energy induced by the collision between alkali-metal atoms and the surface coating. They established that the energy dissipation on the coating (paraffin) of the cell surface is related to the relaxation rate of the alkali-metal (Cs atom) vapour cell: The energy dissipation is directly proportional to the square root of the relaxation rate (or inversely proportional to the square root of relaxation time).…”
Section: Introductionmentioning
confidence: 99%